DETERMINANT FACTORS ON PERSONAL HYGIENE IN THE PREVENTION OF COVID19 IN THE COMMUNITY OF BENGKALIS REGENCY, RIAU, IN 2021 - Ratih Zahratul Jannah; Ela Laelasari (JURNAL KESEHATAN LINGKUNGAN, 2022)
Introduction: The prevalence of personal hygiene behavior in the Riau community in 2018 remains below 39.9%. Therefore, this study aims to identify the determinants of personal hygiene in preventing Covid19 among the residents of Bengkalis Regency, Riau. Methods: Data was collected online in March 2021 from 214 respondents regarding their age, gender, educational history, personal hygiene, infrastructure, accessibility, information exposure, family support, social support, and level of knowledge. The descriptive quantitative study was used with a cross-sectional design and the Chi-square test. Results and Discussion: The results showed that from 214 respondents, those with good and poor personal hygiene are 139 (65%) and 75 (35%) individuals, respectively. The factors that have a statistical relationship with personal hygiene (p<0.05) are age, gender, infrastructure, accessibility, information exposure, family support, and social support, with p-values of 0.000, 0.005, 0.000, 0.000, 0.000, 0.000, and 0.000, respectively. Meanwhile, variables of knowledge and educational history with p values of 0.664 and 0.810, respectively, were not statistically related. Conclusion: Efforts to promote personal hygiene for the prevention of the pandemic include health worker education on Covid19 information, especially the risk factors and how to correctly use masks.